Implementation of School Principal Academic Supervision - Adlina, Fadiah (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2022)
Academic supervision is one of the most important steps for a school in order to improve the quality of educational process. As one of the best role model high schools in Bantul Yogyakarta, MAN Wonokromo has implemented the academic supervision regularly on its own way that might be different from other schools. This study aims to examine the implementation of academic supervision and the obstacles faced by the school principal and how he offers solutions. This field research takes the case in MAN Wonokromo Bantul Yogyakarta using qualitative descriptive approach. The methods used in data collection are observation, interviews and documentation, Meanwhile, testing the validity of the data uses data triangulation techniques. Then, data analysis technique uses data collection, data  reduction, data display and conclusion. The results of this study indicate that the implementation of the principal academic supervision in MAN Wonokromo is done through scheduled and unscheduled planning, and the implementation uses the type of individual supervision in the form of class visits assisted by senior teachers who are in accordance with their scientific fields. The research finding points out that there are innovation and creativity initiated by the school principal in providing solutions when facing obstacles in the implementation of academic supervision by representing the supervision activities to senior teachers. Thus, this kind of supervision actually can be a good example for other schools to keep the quality of learning process in the class.